Genetics and genomics in Peru: Clinical and research perspective. Issue 6 (25th December 2018) - Guio, Heinner; Poterico, Julio A.; Levano, Kelly S.; Cornejo‐Olivas, Mario; Mazzetti, Pilar; Manassero‐Morales, Gioconda; Ugarte‐Gil, Manuel F.; Acevedo‐Vásquez, Eduardo; Dueñas‐Roque, Milagros; Piscoya, Alejandro; Fujita, Ricardo; Sanchez, Cesar; et al.
Abstract : Peruvians currently preserve in their DNA the history of 2.5 million years of human evolution and 150, 000 years of migration from Africa to Peru or the Americas. The development of Genetics and Genomics in the clinical and academic field is shown in this review.